The osteogenic differentiation of rat bone marrow stromal cells cultured with dexamethasone-loaded carboxymethylchitosan/poly(amidoamine) dendrimer nanoparticles - Oliveira, Joaquim M. (2009)
There is an increasing interest in developing novel macromolecular vehicles for the intracellular and controlled delivery of bioactive molecules, since they can allow modulation of the cellular functions in a more effective manner ex vivo, and maintain the cellular phenotype in vivo upon re-implantation. The present study was designed to investigate the effect of combining novel dexamethasone-loaded carboxymethylchitosan/ poly(amidoamine) dendrimer (Dex-loaded CMCht/PAMAM) nanoparticles and, both HA and SPCL scaffolds (3D system) on the proliferation and osteogenic differentiation of rat bone marrow stromal cells (RBMSCs) in vitro. A luminescent cell viability assay using RBMSCs was performed for screening cytotoxicity of the developed HA and SPCL scaffolds. Results corroborated previous ones which have demonstrated in vitro, the superior performance of the HA and SPCL scaffolds on supporting cells adhesion and proliferation. Furthermore, this work showed that RBMSCs seeded onto the surface of both HA and SPCL scaffolds differentiate into osteoblasts when cultured in the presence of 0.01 mg ml!1 Dexloaded CMCht/PAMAM dendrimer nanoparticles. In addition, results demonstrated that Dex-loaded CMCht/PAMAM dendrimer nanoparticles combined with the HA enhance osteogenesis by increasing ALP activity and mineralization of the extra-cellular matrix. The pre-incubation of stem cells with these kinds of nanoparticles allows the delivery of Dex inside the cells and directly influences their cellular fate, being a promising new tool to be used in cells and tissue engineering strategies.